MERDEKA DARI SAMPAH, SEBAGAI PRAKTIK SOSIAL DALAM KEHIDUPAN SOSIAL MASYARAKAT PEDULI SAMPAH - Muhamad Rahman Halim; Asep Maulana (Pastabiq : Jurnal Pengabdian Kepada Masyarakat, 2023)
Plastic waste contributes to environmental damage and is one of the main problems in Indonesia. This is due to population growth and lack of public awareness, as well as the recycling of plastic waste. One of them occurred in Cijeruk District in Cipelang Village, due to the lack of land for garbage disposal, many communities have begun dumping garbage in rivers or near residential areas. This article aims to provide information on waste disposal that increases the creativity of the community in Cipelang village, namely how to process plastic waste. This method is done by making crafts and works from used bottles in the form of Beautiful Flower Vases. Therefore, this method effectively helps to reduce plastic waste. This article aims to provide information to help reduce plastic waste in Cipelang village and encourage community creativity to make better use of waste and preserve the environment.